2022
DOI: 10.1136/bmjpo-2022-001588
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of growth monitoring service by mothers of infants in Mettu town, Southwest Ethiopia

Abstract: BackgroundGrowth monitoring (GM) is a preventive activity that serves as the core function in an integrated child health and nutrition programme. In most developing nations, including Ethiopia, however, the use of GM service is insufficient. Hence, the purpose of this study was to evaluate the use of GM services and associated characteristics among mothers of infants in Mettu town, Southwest Ethiopia.ObjectiveTo assess the utilisation of GM service by mothers of infants in Mettu town, Southwest Ethiopia, 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…The result of this study is lower than the study conducted in different parts of Ethiopia, which reported the utilization of GMP services to be 16.9, 25.2, 32.9, and 38.9% (12)(13)(14)(15). This difference may be due to a huge difference in place of delivery (as the health facility delivery for the last child in Banja district was 96.6%, while it was only 46.1% in our study) (12), which enables the mothers to get exposed to more information about the GMP and its advantages.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The result of this study is lower than the study conducted in different parts of Ethiopia, which reported the utilization of GMP services to be 16.9, 25.2, 32.9, and 38.9% (12)(13)(14)(15). This difference may be due to a huge difference in place of delivery (as the health facility delivery for the last child in Banja district was 96.6%, while it was only 46.1% in our study) (12), which enables the mothers to get exposed to more information about the GMP and its advantages.…”
Section: Discussioncontrasting
confidence: 89%
“…This result is slightly higher than the study conducted in Butajira town, southern Ethiopia, which reported the utilization of GMP services to be 11% ( 22). This may be due to the involvement of urban kebeles together with the relatively low number of (four) rural kebeles in our study compared to the study conducted in Butajira, which included a high number of (nine) rural kebeles with no urban kebeles, which has an effect on their utilization of health services (23,24), which in turn affects their exposure to GMP services (14,17).…”
Section: Discussionmentioning
confidence: 78%
“…The utilisation of GMP services demonstrated significant associations with factors such as birthplace, PNC follow-up, participation in regular GMP sessions and wealth status. The utilisation of GMP services is consistent with the findings from Mettu Town (25.2%)26 and from rural northern Ghana (28.5%) 27. This finding indicates a higher prevalence compared with a study conducted in Afar Region (15.9%)28 and southern Ethiopia (16.9%) 21.…”
Section: Discussionsupporting
confidence: 86%